2021
DOI: 10.1371/journal.pone.0246755
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification, and antimicrobial susceptibility pattern of Campylobacter jejuni and Campylobacter coli from cattle, goat, and chicken meats in Mekelle, Ethiopia

Abstract: Campylobacter jejuni and Campylobacter coli are globally recognized as a major cause of bacterial foodborne gastroenteritis. A cross-sectional study was conducted from October 2015 to May 2016 in Mekelle city to isolate, identify, and estimate the prevalence of C. jejuni and C. coli in raw meat samples and to determine their antibiotic susceptibility pattern. A total of 384 raw meat samples were randomly collected from bovine (n = 210), goat (n = 108), and chicken (n = 66), and isolation and identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 53 publications
4
21
0
Order By: Relevance
“…Most Campylobacter species have been isolated from animals, and direct and indirect contact with animals is a known risk factor for Campylobacter infection, especially in children (10)(11)(12). Animals can serve both as reservoirs, and as potential sources for the contamination of food, water, and the environment (4,(13)(14)(15). Contamination of different water sources with Campylobacter species presents an opportunity for transmission of environmentadapted genotypes to livestock and humans (7,13,14,16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most Campylobacter species have been isolated from animals, and direct and indirect contact with animals is a known risk factor for Campylobacter infection, especially in children (10)(11)(12). Animals can serve both as reservoirs, and as potential sources for the contamination of food, water, and the environment (4,(13)(14)(15). Contamination of different water sources with Campylobacter species presents an opportunity for transmission of environmentadapted genotypes to livestock and humans (7,13,14,16).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the prevalence of Campylobacter in Ethiopia have identified a range of 13.8-50.0% in humans, and 10.6-56.5% in animals (12,13,(22)(23)(24)(25)(26)(27). In addition, studies conducted on the antimicrobial susceptibility profiles of Campylobacter species, in both humans and animals in Ethiopia, have identified increased multidrug resistance of Campylobacter species (4,25,28). Most of these studies were conducted in only humans or animals, and utilized only a culture method approach for Campylobacter species identification and characterization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 15 In Ethiopia, it is difficult to give an accurate picture of the disease’s burden mainly due to lack of a national surveillance program, limited routine culture availability for Campylobacter species isolation in clinical and research settings, and the requirement for selective media. 16 …”
Section: Introductionmentioning
confidence: 99%
“…14,15 In Ethiopia, it is difficult to give an accurate picture of the disease's burden mainly due to lack of a national surveillance program, limited routine culture availability for Campylobacter species isolation in clinical and research settings, and the requirement for selective media. 16 Children, the elderly, and those with weakened immune systems (such as cancer patients, HIV/AIDS patients, and transplant recipients) are particularly vulnerable. Because of the severity of diarrhea and the possibility of squeals, campylobacteriosis is a major public health threat having a significant socioeconomic implications.…”
Section: Introductionmentioning
confidence: 99%